Sheet operation based block decomposition of solid models for hex meshing. (April 2017) - Wang, Rui; Shen, Chun; Chen, Jinming; Wu, Haiyan; Gao, Shuming
Abstract: High quality hex mesh can be effectively generated based on a block structure of a solid model, but existing approaches to block decomposition of the solid model are still far from expectations. In this paper, we propose a new method to decompose the solid model into a block structure using sheet operations, which guarantees the validity of the resulting block structure. The method first generates an initial hex mesh of a given solid model based on its tet mesh. Then, a number of fundamental sheets and high-quality curve-related sheets are inserted on the boundary and inside the initial hex mesh respectively by sheet inflation to capture the geometry of the solid model. Finally, a reasonable and valid block structure for the solid model is obtained by extracting all of the original sheets as a whole as well as an optimal deletable sheet set determined by quality prediction. Experimental results prove the effectiveness of the proposed method. Highlights: A method to automatically generate block structure of a solid model for hex meshing. Sheet operations ensure topological validity of the obtained block structure. Fundamental and curve-related sheet insertion ensures geometric validity. The optimal deletable sheet set is extracted to ensure good topological quality.